Functional characterization, homology modeling and docking studies of beta-glucosidase responsible for bioactivation of cyanogenic hydroxynitrile glucosides from Leucaena leucocephala (subabul) - Shaik, Noor M.; Misra, Anurag; Singh, Somesh; Fatangare, Amol B.; Ramakumar, Suryanarayanarao; Rawal, Shuban K.; Khan, Bashir Mohammad (Molecular Biology Reports, 2013)
Glycosyl hydrolase family 1 beta-glucosidases are important enzymes that serve many diverse functions in plants including defense, whereby hydrolyzing the defensive compounds such as hydroxynitrile glucosides. A hydroxynitrile glucoside cleaving beta-glucosidase gene (Llbglu1) was isolated from Leucaena leucocephala, cloned into pET-28a (+) and expressed in E. coli BL21 (DE3) cells. The recombinant enzyme was purified by Ni-NTA affinity chromatography. The optimal temperature and pH for this beta-glucosidase were found to be 45 A degrees C and 4.8, respectively. The purified Llbglu1 enzyme hydrolyzed the synthetic glycosides, pNPGlucoside (pNPGlc) and pNPGalactoside (pNPGal). Also, the enzyme hydrolyzed amygdalin, a hydroxynitrile glycoside and a few of the tested flavonoid and isoflavonoid glucosides. The kinetic parameters K (m) and V (max) were found to be 38.59 mu M and 0.8237 mu M/mg/min for pNPGlc, whereas for pNPGal the values were observed as 1845 mu M and 0.1037 mu M/mg/min. In the present study, a three dimensional (3D) model of the Llbglu1 was built by MODELLER software to find out the substrate binding sites and the quality of the model was examined using the program PROCHEK. Docking studies indicated that conserved active site residues are Glu 199, Glu 413, His 153, Asn 198, Val 270, Asn 340, and Trp 462. Docking of rhodiocyanoside A with the modeled Llbglu1 resulted in a binding with free energy change (Delta G) of -5.52 kcal/mol on which basis rhodiocyanoside A could be considered as a potential substrate.
Keywords: Glycosyl hydrolase family 1; homology modeling; Leucaena leucocephala; Molecular docking

Probing the active site of cinnamoyl CoA reductase 1 (Ll-CCRH1) from Leucaena leucocephala - Sonawane, Prashant; Patel, Krunal; Vishwakarma, Rishi Kishore; Srivastava, Sameer; Singh, Somesh; Gaikwad, Sushama M.; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2013)
Lack of three dimensional crystal structure of cinnamoyl CoA reductase (CCR) limits its detailed active site characterization studies. Putative active site residues involved in the substrate/NADPH binding and catalysis for Leucaena leucocephala CCR (Ll-CCRH1; GenBank: DQ986907) were identified by amino acid sequence alignment and homology modeling. Putative active site residues and proximal H215 were subjected for site directed mutagenesis, and mutated enzymes were expressed, purified and assayed to confirm their functional roles. Mutagenesis of S136, Y170 and K174 showed complete loss of activity, indicating their pivotal roles in catalysis. Mutant S212G exhibited the catalytic efficiencies less than 10% of wild type, showing its indirect involvement in substrate binding or catalysis. R51G, D77G, F30V and I31N double mutants showed significant changes in K-m values, specifying their roles in substrate binding. Finally, chemical modification and substrate protection studies corroborated the presence Ser, Tyr, Lys, Arg and carboxylate group at the active site of Ll-CCRH1. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Chemical modification; Cinnamoyl CoA reductase 1; Docking simulations; homology modeling; Site directed mutagenesis; Substrate protection